Triterpenoids from The Bark of Garcinia porecta and their Cytotoxic Activity against MCF7 Breast Cancer Lines - Kansy Haikal; Darwati Darwati; Alya Tsamrotul; Tati Herlina; Tri Mayanti; Nurlelasari Nurlelasari; Unang Supratman (ALCHEMY Jurnal Penelitian Kimia, 2019)
The Garcinia genus is a well known tropical plant in the Indo-Malesiana region and mainly distributed in tropical countries including Indonesia, Thailand, and Malaysia. Previous phytochemical studies on Garcinia species have led to the identification and isolation of mainly prenylated xanthones. This research describes the isolation and structure elucidation of isolated triterpenoids compounds from the bark of Garcinia porecta. Dried powder bark of G. porecta was extracted with methanol and then partitioned with n-hexane, ethyl acetate, and n-butanol. The n-hexane extract then was separated and purified with chromatography techniques to obtain isolated compounds 1 and 2. The chemical structure of isolated compounds was elucidated by spectroscopic methods including one and two-dimensional NMR as well as high-resolution mass spectrometric analysis and identified as lanosterol (1) dan arabidiol (2), respectively. These triterpenoids were isolated from this plant for the first time. Compound 1 and 2 showed weak cytotoxic activity against MCF-7 breast cancer cells with IC50 values of 60.09 dan 46.17 µM, respectively.